Perbedaan Motivasi Belajar Bahasa Arab Mahasiswa PAI - Wedra Aprison; Syawaluddin Syawaluddin (Universitas Pahlawan Tuanku Tambusai, 2022)
Students' motivation is various and not sufficient, meanwhile Arabic is an obligation in the program of study PAI.This research determined the Arabic language learning motivation based school origins of the Islamic Education Study Program. The approach used is comparative quantitative. The population is 200 students. While data analysis used anova analaysis.The results found that the Arabic learning motivation of the students who graduated from Senior High Schools was categorized as moderate, S. The obtained percentage for this category was 70.62%. On the other hand, the students who graduated from Islamic Senior High School were categorized as high, T. The obtained percentage was 74.27%. The hypothesis test obtained a significant difference, indicated by the probability value of 0.017, lower than 0.05. The result asserted that guidance and counseling service was important to improve the Arabic learning motivation for the students of Islamic Study Program.